Autoria e textualização: humor nos processos de inscrição discursiva na constituição autoral de Tutty Vasques - Chagas, Diogo Silva (2017)
Joining the theoretical framework of French Line Discourse Analysis, more precisely, to the reflections proposed by Maingueneau and Possenti, this work is developed from the studies on authorship and humour. For Maingueneau (2010), there are three different dimensions in relation to the notion of author: (i) the author-guarantor; (ii) the author-actor and (iii) the author-auctor. Maingueneau (2006; 2010) also uses the concept of paratopic creating, which refers to a development of three instances that forge the authorial construction; the instances are those of inscriber, writer and person. Considering this, Maingueneau (2010) understands that from this creative process emerges an image of author, which may be related to any of those dimensions of author (author-guarantor, author-actor, author-auctor). In addition, this work is developed taking into account what Possenti (2009) proposes as being signs of authorship, a proposal of analysis that understands that authorship can only be understood at a discursive level, by the signs. In relation to humour and humorous texts, we have recourse to the propositions of Raskin (1985) and Possenti (1998; 2013). We understand, in this work, that humour is due to the overlapping of scripts and that, in this overlapping, observable in the textualization, it is possible to observe the signs of authorship in operation. The corpus of this research groups texts from October to December 2014 written by Tutty Vasques for Tutty Humor (Tutty Humour) column on O Estado de S. Paulo newspaper, for the blog Tutty Humor: má notícia é a maior diversão (Tutty Humor: bad news is the biggest fun) on Portal Estadão, and the texts of his Twitter account, @tuttyvasques. The selected texts have similar characteristics: (i) they are mostly concise and (ii) they provoke a humorous effect always related to events which are contemporaneous with their publications. Taking into account the style of the author and the materialization of polemic discourses, the analysis of the corpus intends to show which image of author is emerged in relation to Tutty Vasques.